1986
DOI: 10.1172/jci112467
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial hyperglycemia in patients with noninsulin-dependent diabetes mellitus. Role of hepatic and extrahepatic tissues.

Abstract: Patients with noninsulin-dependent diabetes mellitus (NIDDM) have both preprandial and postprandial hyperglycemia. To determine the mechanism responsible for the postprandial hyperglycemia insulin secretion, insulin action, and the pattern of carbohydrate metabolism after glucose ingestion were assessed in patients with NIDDM and in matched nondiabetic subjects using the dual isotope and forearm catheterization techniques. Prior to meal ingestion, hepatic glucose release was increased (P < 0.001) in the diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
240
2
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(268 citation statements)
references
References 40 publications
24
240
2
1
Order By: Relevance
“…Two strategies can be used to overcome this problem. The first is to fit the tracer data either to equation (1), or its solution (3). When this is done, spurious errors in slope are eliminated and the calculations of R a (and R d ) show a consistent pattern for the duration of the study, as illustrated in the studies shown here.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Two strategies can be used to overcome this problem. The first is to fit the tracer data either to equation (1), or its solution (3). When this is done, spurious errors in slope are eliminated and the calculations of R a (and R d ) show a consistent pattern for the duration of the study, as illustrated in the studies shown here.…”
Section: Discussionmentioning
confidence: 91%
“…After the determination of k from equation (2), R a was determined from equation (1). The rate of glucose disappearance or utilization, R d , was then calculated as:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fasting blood glucose levels are mainly determined by the rate of endogenous glucose production [38]. Postprandial changes in glucose concentrations, however, are related to numerous factors, including glucose uptake by skeletal muscle and peripheral insulin sensitivity, as well as by the rate of endogenous glucose production [38,39]. Given the relative paucity of hepatic IGF-I receptors [40], our observation is consistent with IGF-I mainly influencing peripheral glucose uptake in the postprandial state, either directly or indirectly via its effects on the action of insulin to dispose of glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Despite intensive work, the fate of oral glucose remains surprisingly controversial. Reports of the cumulative appearance of oral glucose in plasma have varied from about 70% (34,35) to nearly 100% (36,37), and the maximal rates of glucose appearance have varied about 2-fold. Livesey et al (36) reported a study of glucose kinetics in 12-h fasted humans after an oral glucose load, using stable isotopes and mass spectrometry to detect gastric absorption of [ 13 C 6 ]glucose oral glucose.…”
Section: Discussionmentioning
confidence: 99%